Holocene paleotemperature reconstruction based on phytolith records of lacustrine sediments in the Badain Jaran Desert, northwestern China - Wang, Yixin; Ning, Kai; He, Qinghua; Jie, Dongmei; Guan, Qingyu (Frontiers in Earth Science, 2022)
Quantitative reconstruction of regional paleotemperature is the key to understanding temperature change and its driving mechanisms. In this study, 133 phytolith samples were collected as proxy indicators from lacustrine sediments of the Zhunzhahanjilin (ZZH) profile in the hinterland of the Badain Jaran Desert, China. The phytolith samples were then analyzed to quantitatively reconstruct the Holocene paleotemperature at the millennial scale. Based on accelerator mass spectrometry (AMS), 14C dates and an ordered clustering method were used to divide the phytoliths into five assemblage zones with environmental significance. The quantitative reconstruction results indicated that the paleotemperature in the Badain Jaran Desert was relatively high during the early Holocene (11,040–8,200 cal a BP), and the average paleotemperature was approximately 9.5°C. This may have led to increased melt water near the surrounding area and recharged the lakes in the Badain Jaran Desert, resulting in the expansion of the lakes during the early Holocene. The average paleotemperature during the middle Holocene (8,200–3,100 cal a BP) was approximately 7.9°C. This period was warm and the environment was humid, with extensive precipitation from summer monsoons and low evaporation leading to higher water levels in the lakes. The paleotemperature decreased during the late Holocene (3,100 cal a BP to the present), and lakes retreated or dried up because of the decreased summer monsoon rains. The Holocene paleotemperature in the Badain Jaran Desert may have been related to July insolation in the Northern Hemisphere and had a range of impacts on the hydrological cycle in this arid region.